IMPLEMENTASI PEMBELAJARAN LANGSUNG (INSTRUKSI LANGSUNG) PADA PROGRAM TPQ DI LPKA KELAS II BENGKULU - Astuti, Puji astuti; Palenti, Citra dwi; Gusti, Ririn (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the implementation of Direct Instruction in the TPQ program for juvenile inmates at LPKA class II Bengkulu. The research employed qualitative descriptive approach with data collected through observation, interviews, and documentation. Participants included TPQ teachers, LPKA officials, and TPQ participant inmates. findings show that Direct Instruction in the TPQ program is implemented systematically, starting from the delivery of learning objectives, teacher led demonstrations, intensive guidance, comprehension checks through questions or memorization, to independent assignments. The instructional strategies are adapted to the inmate conditions, who are not allowed to bring writing tools into their cells, thus focusing the material on memorization and direct practice. The TPQ program not only emphasizes the mastery of Qur’an reading but also shapes inmate character and morals through regular worship practices, memorization of short surahs, and instilling Islamic values. Challenges faced include limited time, facilities, and varying learning abilities among participants.